Cascading effects of disaster-related CO exposures during pregnancy. (December 2022) - Dodd-Butera, Teresa; Li, Hong; Beaman, Margaret; DerMovsesian, Mary; Pritty, Molly Broderick; Clark, Richard F.; Chambers, Christina D.
Abstract: Disaster-related carbon monoxide (CO) poisoning can occur in the event of extended power loss and subsequent use of makeshift heating and cooking elements in poorly ventilated spaces. The maternal-fetal dyad represents populations highly vulnerable to disasters and the subsequent compounding effects of CO poisoning. This study synthesizes evidence related to disaster-associated global CO exposures, reports of CO exposures in pregnancy, and associated individual outcomes in the maternal-fetal dyad. Implications related to UNDRR include Sendai Priorities I and IV: understanding associated risks and disaster risk reduction strategies to reduce the incidence of CO poisoning in vulnerable populations. Highlights: Disaster risk reduction strategies include awareness and prevention of CO poisoning. The maternal-fetal dyad is susceptible to the effects of CO exposure post-disaster. Disaster-related CO poisoning may occur after storms and power loss. Makeshift heating and cooking with poor ventilation increase risk for CO poisoning. CO detectors offer a strategy for prevention and warning for risky indoor CO levels.